As crônicas da infância na série Para Gostar de Ler: uma perspectiva semiótica - Farias, Naiana Iris Teixeira (2017)
The image of childhood is outlined in the chronicles titled Para Gostar de ler, a historical children's series released by editor Jiro Takahashi in 1977. In the first volume, the preface proposes a pact of complicity between narrator and narratary, which is treated by the vocative "Student friend". In addition, since the introduction, the book has made it clear that its main purpose was to encourage students to read and not to teach grammar and wording. In the context of Comparative Studies, this work presents a survey of the first five volumes, which serve as corpus for the present investigation, examined in the light of Discursive Semiotics, based on the analytical category of polemical Statement, according to Greimas and Courtés (2008). In the comparison between the chronicles of the authors of the series (Carlos Drummond de Andrade, Fernando Sabino, Rubem Braga and Paulo Mendes Campos), it is inferred that there is an asymmetrical relationship between children and adults, in which unilateral and bilateral contracts are established, sometimes positive (seduction and temptation), sometimes negative (provocation or threat). This relation is presented in the chronicles from the different perspectives of the writers in question, thus observing associations and dissociations with regard to childishness, due to the very multi-faceted character of the notion of childhood, in which the different forms encountered by the subjects to persuade the other to achieve their personal goal. However, the bias of the series, frankly favorable to children's actors, subverts the alleged asymmetry imposed by the logic of the adult world.